2018
DOI: 10.1007/s12088-018-0723-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antimicrobial Properties of Silver Nanoparticles Synthesized from Selected Bacteria

Abstract: Green silver nanoparticle (AgNP) biosynthesis is facilitated by the enzyme mediated reduction of Ag ions by plants, fungi and bacteria. The antimicrobial activity of green AgNPs is useful to overcome the challenge of antimicrobial resistance. Antimicrobial properties of biosynthesized AgNPs depend on multiple factors including culture conditions and the microbial source. The antimicrobial activity of AgNPs biosynthesized by ATCC 27853, ATCC 25922, ATCC 25923 and (confirmed clinical isolate) were investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
5
28
0
Order By: Relevance
“…14 Further characterization of biosynthesized AgNPs using FT-IR spectroscopy indicated NH stretch vibrations present in the amide linkages of primary and secondary amines of proteins, presence of nitrocompounds from proteins or enzymes, C-H symmetrical stretch vibration of alkanes and -C-N-stretching vibrations confirming that the attached proteins in the biosynthesized AgNPs support stabilization of AgNPs. 15 In the present study, silver nanoparticles synthesised by all four bacterial species demonstrated over 50% biofilm inhibition at a AgNP concentration between 1.98 mg/ml to 0.225 mg/ml (Fig. 3).…”
Section: Discussionsupporting
confidence: 56%
“…14 Further characterization of biosynthesized AgNPs using FT-IR spectroscopy indicated NH stretch vibrations present in the amide linkages of primary and secondary amines of proteins, presence of nitrocompounds from proteins or enzymes, C-H symmetrical stretch vibration of alkanes and -C-N-stretching vibrations confirming that the attached proteins in the biosynthesized AgNPs support stabilization of AgNPs. 15 In the present study, silver nanoparticles synthesised by all four bacterial species demonstrated over 50% biofilm inhibition at a AgNP concentration between 1.98 mg/ml to 0.225 mg/ml (Fig. 3).…”
Section: Discussionsupporting
confidence: 56%
“…Bacteria, fungi and plants have recently gained much attention due to their ability to biosynthesize metal NPs by an environmentally friendly process. For example, silver nanoparticles have been successfully made from Staphylococcus aureus, Pseudomonas aeruginosa, 7 Escherichia coli, Acinetobacter species, 8 Lactobacillus species, 9 Klebsiella pneumoniae 10 and Enterobacter cloacae 11 . An advantage of biological synthesis methods is the higher stability of the AgNPs compared to chemically synthesized NPs.…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Against A. baumannii, BkCE-AgNPs showed higher ZOI than standard streptomycin of the same concentration and higher inhibition zone than AgNPs synthesis using Discorea bulbifera (Chopade et al 2013). BkCE-AgNP ZOI against P. aeruginosa was equal to AgNPs synthesized using Ipomea carnea (Daniel et al 2014)) and more than AgNPs synthesized using E. coli and S. aureus (Peiris et al 2018). BkCE-AgNPs showed a 13.5 mm ± 0.5 zone against S. aureus, which was more signi cant than the chemically synthesized AgNPs using sodium borohydride (Vu et al 2018).…”
Section: Antimicrobial Testing By Disc Diffusion Methodsmentioning
confidence: 88%